2012
DOI: 10.1097/dad.0b013e31823f9194
|View full text |Cite
|
Sign up to set email alerts
|

Acrokeratosis Verruciformis of Hopf Showing P602L Mutation in ATP2A2 and Overlapping Histopathological Features With Darier Disease

Abstract: The relationship between acrokeratosis verruciformis (AKV) of Hopf and Darier disease (DD) has been debated for several decades. Both diseases are now thought to result from mutations in the same gene, that is, the ATP2A2 gene encoding the sarco (endo) plasmic reticulum Ca ATPase2 pump (SERCA2), although their histopathological features are different. We sought to detect possible overlapping histopathological features between AKV and DD. Fourteen members of a family affected by AKV were analyzed for the underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
3
9
0
1
Order By: Relevance
“…The unique finding of AVH is of a church spire, while DD uniquely exhibits suprabasal dyskeratosis with corps ronds and grains in histopathological examination . However, as in our case, histopathological studies on serial sections obtained from AVH lesions have demonstrated certain histopathological features that overlap with those of DD . In our case, the histopathological findings of compact hyperkeratosis, hypergranulosis, slight acanthosis, and circumscribed epidermal elevations resembling church spires were consistent with AVH, but there was also the DD‐like finding of a cleft in the granular layer with several acantholytic keratinocytes.…”
Section: Reportsupporting
confidence: 52%
“…The unique finding of AVH is of a church spire, while DD uniquely exhibits suprabasal dyskeratosis with corps ronds and grains in histopathological examination . However, as in our case, histopathological studies on serial sections obtained from AVH lesions have demonstrated certain histopathological features that overlap with those of DD . In our case, the histopathological findings of compact hyperkeratosis, hypergranulosis, slight acanthosis, and circumscribed epidermal elevations resembling church spires were consistent with AVH, but there was also the DD‐like finding of a cleft in the granular layer with several acantholytic keratinocytes.…”
Section: Reportsupporting
confidence: 52%
“…The mutation identified in our patient was previously reported in an Italian patient with germline Darier disease manifesting as acrokeratosis verruciformis with nail changes . There is evidence that acrokeratosis verruciformis and Darier disease are allelic disorders with variable expression of overlapping features . Mutations in the same codon of ATP2A2 have resulted in clinical phenotypes of acrokeratosis verruciformis and Darier disease in separate individuals .…”
Section: Discussionsupporting
confidence: 57%
“…27 There is evidence that acrokeratosis verruciformis and Darier disease are allelic disorders with variable expression of overlapping features. 28 Mutations in the same codon of ATP2A2 have resulted in clinical phenotypes of acrokeratosis verruciformis and Darier disease in separate individuals. 29 The p.706D>N mutation falls within a domain regulating enzymatic phosphorylation required for calcium conductance and is known to reduce phosphorylation rate and calcium flux.…”
Section: Discussionmentioning
confidence: 99%
“…However, two families and one sporadic patient suffered from AKV rather than generalized DD, caused by mutations p.(Pro602Leu) and p.(Leu590Pro), respectively (see Table 1). These mutations, as well as variant p.(Ala698Val), have been reported in association with the AKV phenotype before [Dhitavat et al, 2003b;Berk et al, 2010;Bergman et al, 2012;Nellen et al, 2015]. All mutations are found in exon 14, encoding the ATPbinding domain of SERCA2.…”
Section: Genotype-phenotype Correlation In Ddmentioning
confidence: 93%